Diagnosis and Improvement of the Collective Irrigation and Drainage Services in Water Users' Associations of Calabria (Southern Italy)†. (7th August 2018) - Zema, Demetrio Antonio; Nicotra, Angelo; Zimbone, Santo Marcello
Abstract: There is a need of diagnostic processes of collective irrigation and drainage services in southern Italy, helping to identify the weak points of management and to suggest improving actions. To these aims, a comprehensive analysis of the collective services in the water users' associations (WUAs) operating in Calabria has been carried out, covering the infrastructural, organization and management aspects. The investigation has shown important shortcomings: (i) the old and small irrigation systems need renovation; (ii) the drainage service would benefit from a continuous and planned maintenance activity of the hydraulic network; (iii) a rational reorganization of WUA human resources together with education activities is suggested. Management of WUAs (affected by low service levels and economic imbalance) needs improvement in procedures of water distribution (from rotational scheduling to on‐demand delivery) and water charging (with taxation on actual water consumption instead of on irrigable area), together with reduction of fee evasion and integration of profits (e.g. through sale of hydroelectric energy by small turbines installed in the irrigation networks). This survey proposes a methodological framework which could be a technical and scientific support broadened to all aspects influencing irrigation and drainage activities of collective agencies and transferable to other rural contexts. © 2018 John Wiley & Sons, Ltd.